Cold-formed tubular members and connections : structural behaviour and design - Zhao, Xiao-Ling (Elsevier, 2005)
Cold formed structural members are being used more widely in routine structural design as the world steel industry moves from the production of hot-rolled section and plate to coil and strip, often with galvanised and/or painted coatings. Steel in this form is more easily delivered from the steel mill to the manufacturing plant where it is usually cold-rolled into open and closed section members. This book not only summarises the research performed to date on cold form tubluar members and connections but also compares design rules in various standards and provides practical design examples.